2018
DOI: 10.1128/mbio.02449-17
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya Virus Strains Show Lineage-Specific Variations in Virulence and Cross-Protective Ability in Murine and Nonhuman Primate Models

Abstract: Chikungunya virus (CHIKV) is a reemerging arbovirus capable of causing explosive outbreaks of febrile illness, polyarthritis, and polyarthralgia, inflicting severe morbidity on affected populations. CHIKV can be genetically classified into 3 major lineages: West African (WA); East, Central, and South African (ECSA); Indian Ocean (IOL); and Asian. Additionally, the Indian Ocean (IOL) sublineage emerged within the ECSA clade and the Asian/American sublineage emerged within the Asian clade. While differences in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 43 publications
3
81
0
2
Order By: Relevance
“…Previous studies have shown that viremia in A129 mice occurs on days 1-3 [15]. Therefore, to determine if the vaccine could protect against viremia, blood was taken from all mice on day 2 post challenge, which corresponds to the predicted day of peak viremia [15]. Consistent with survival and foot swelling, only the mice that were PBS-treated or ChAdOx1 Zika-vaccinated had a viremia of approximately 6 log10 pfu/mL ( Figure 5).…”
Section: Chadox1 Chik and Chadox1 Chik δCap Protect From Lethal Chikvmentioning
confidence: 79%
See 4 more Smart Citations
“…Previous studies have shown that viremia in A129 mice occurs on days 1-3 [15]. Therefore, to determine if the vaccine could protect against viremia, blood was taken from all mice on day 2 post challenge, which corresponds to the predicted day of peak viremia [15]. Consistent with survival and foot swelling, only the mice that were PBS-treated or ChAdOx1 Zika-vaccinated had a viremia of approximately 6 log10 pfu/mL ( Figure 5).…”
Section: Chadox1 Chik and Chadox1 Chik δCap Protect From Lethal Chikvmentioning
confidence: 79%
“…All ChAdOx1 CHIKV-vaccinated mice were protected in this model, even at a high challenge dose, highlighting the robustness of the single-dose vaccination. Furthermore, high titer viremias are produced from CHIKV infection in A129 mice [15], and ChAdOx1 CHIKV vaccines were able to reduce challenge viremia levels to undetectable levels on the day of highest anticipated titer. This feature is critical for arbovirus vaccines as it decreases the potential for mosquito transmission.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations